Methodological Aspects of Dream Intervention Modes Referred to in Pass Testimonies from Lacanian Schools Affiliated with the WAP and the SPFLF - Labaronnie, Ma. Celeste (2020)
Objective. This paper presents a study of dream intervention modes referred to in pass testimonies from Lacanian Schools affiliated with the World Association of Psychoanalysis and the School of Psychoanalysis of the Forums of the Lacanian Fields. Method. The intentional sample consists of 80 testimonies, obtained from the publications of each school. From that point, we analyzed qualitatively 14 examples, in which the intervention of the analyst over a dream story was explicit. Results. We could find varied interventions and gather them into four main ideas: (a) interrogation or invitation to associate; (b) interpretation; (c) cut; (d) other analytic act variations. As a conclusion, the Freudian approach with dreams is still in effect, but we also observe some others ways to intervene that aim beyond sense: to letter and to cut, as the foundations of psychoanalytic interpretation.